Pitfalls and protocols in DEA - R. G. Dyson (2001)
The practical application of data envelopment analysis (DEA) presents a range of procedural issues to be examined and resolved including those relating to the homogeneity of the units under assessment, the input/output set selected, the measurement of those selected variables and the weights attributed to them. Each of these issues can present difficulties in practice. The purpose of this paper is to highlight some of the pitfalls that have been identified in application papers under each of these headings and to suggest protocols to avoid the pitfalls and guide the application of the methodology.